Cytokines/Chemokines: Potential Biomarkers for Non-paraneoplastic Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Liu, Jingwen; Liu, Lei; Kang, Wenting; Peng, Gongxin; Yu, Di; Ma, Qiuying; Li, Yatong; Zhao, Yan; Li, Lin; Dai, Feifei; Wang, Jiawei (Frontiers in Neurology, 2020)
Objective: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the most common type of autoimmune encephalitis. This study focusses on finding new biomarkers to evaluate the clinical condition and providing new directions for treatment. Methods: 44 cytokines/chemokines were measured in cerebrospinal fluid of 10 non-paraneoplastic patients and 9 controls. We selected some of cytokines/chemokines that significantly increased in patients. Six selected cytokines/chemokines including IL-10, CXCL10, CCL22, CCL3, IL-7, TNF-α and three previously reported (IL-2, IL-6, and IL-17A), were measured in 7 other patients who provided repeat samples. We compared their levels, and explored correlations with severity of disease and antibody titers. Results: The levels of Th1 axis (CXCL10, TNF-α, IFN-γ, CCL3), Th2 axis (CCL1, CCL8, CCL17, CCL22), Treg axis (IL-10), Th17 axis (IL-7), and B cell axis (CXCL13) cytokines, as well as IL-12 p40 and IL-16, were significantly higher in patients compared to controls. The level of IL-2 was significantly decreased at the intermediate stage of treatment compared with before treatment. Severity of disease is positively correlated with levels of CXCL10, CCL3, IL-10, CCL22, and IL-6. The level of CCL3 in the high antibody titer group were greater than the low antibody titer group. Conclusion: The pathogenesis of anti-NMDAR encephalitis involves T cell and B cell cytokines. T cells likely assist B cells to produce antibody. IL-2, CXCL10, CCL3, IL-10, CCL22, and IL-6 may represent new biomarkers in anti-NMDAR encephalitis. Given the lack of research on IL-10, CCL3, and CCL22 in this disease, it will be informative to explore their potential role in pathogenesis in larger studies.